Inheritance patterns of male asexuality in hybrid males of a water frog Pelophylax esculentus - Doležálková-Kaštánková, Marie; Dedukh, Dmitrij; Labajová, Veronika; Pustovalova, Eleonora; Choleva, Lukáš (Scientific reports, 2024)
Gametogenesis produces gametes as a piece of genetic information transmitted to the offspring. While during sexual reproduction, progeny inherits a mix of genetic material from both parents, asexually reproducing organisms transfer a copy of maternal or paternal DNA to the progeny clonally. Parthenogenetic, gynogenetic and hybridogenetic animals have developed various mechanisms of gametogenesis, however, their inheritance is not fully understood. Here, we focused on the inheritance of asexual gametogenesis in hybrid Pelophylax esculentus (RL), emerging after crosses of P. lessonae (LL) and P. ridibundus (RR). To understand the mechanisms of gametogenesis in hybrids, we performed three-generation experiments of sexual P. ridibundus females and hybrids from all-male hybrid populations. Using fluorescent in situ hybridization, micronuclei analysis, flow cytometry and genotyping, we found that most adult hybrid males simultaneously produced two types of clonal sperm. Also, most male tadpole progeny in two successive backcrossed generations simultaneously eliminated L and R parental genomes, while some progeny produced only one type of sperm. We hypothesize that the reproductive variability of males producing two kinds of sperm is an adaptive mechanism to reproduce in mixed populations with P. ridibundus and may explain the extensive distribution of the all-male lineage across the European River Basin.
Keywords: hybridizace genetická; Animals; Male hybridogenesis; Genotype; Female; spermie; Rana esculenta; ženské pohlaví; Spermatozoa; Crossing experiments; Ranidae; FISH.; genotyp; Hybridization, Genetic; Micronuclei; nepohlavní rozmnožování; typy dědičnosti; Male; Inheritance Patterns; Monospermic; hybridizace in situ fluorescenční; mužské pohlaví; zvířata; In Situ Hybridization, Fluorescence; Reproduction, Asexual; Amphispermy; Spermatogenesis